ANALISA NIAT MITRA PENJUAL UNTUK MENGGUNAKAN APLIKASI PENGIRIMAN MAKANAN SECARA DARING - Renza Fahlevi (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2023)
The presence of new variant of the covid 19 Omicron virus will certainly leads to the public alert. In order to prevent transmission, the government recommends that people should reduce direct interactions between individuals. This condition is an opportunity for companies providing Online Food Delivery Applications (OFDA) to take benefit from increased transactions which occur during COVID-19 pandemic. Currently, research on OFDA is still focused on OFDA consumers as a research’s Objects. On the other hand, the OFDA provider companies benefit from the profit sharing provided by food and beverage sellers who sell their products at APMSD. The results of this research are believed to be able to help APMSD companies in developing effective marketing strategies in order to attract sales partners to continue using OFDA. This research uses five independent variables, namely performance expectancy, effort expectancy, social influence, trust and price value. Data processing using SPSS application involving sample size of 158 respondents. This study reveals that social influence, trust and price value have a positive significant effect on intention to use OFDA. While two other independent namely Performance expectancy, Effort expectancy does not have significant influence to the dependent variable.